Improving Energy Efficiency in Wastewater Treatment. Identification of Key Parameters and Key Performance Indicators - Campo Moreno, Pablo (Cranfield University, 2018)
In this presentation we propose to identify relevant parameters (key performance indicators, KPIs) that better describe the performance of a given treatment stage along with its corresponding energy demand. The final goal for compiling KPIs is the calculation of the Water Treatment Energy Index. This index evaluates the energy efficency in wastewater treatment plants and will allow one to readily compare energy utilization from different plants in a systematic way.
Keywords: Energy'; 'wastewater'; 'KPIs'; 'treatment'; 'Environmental Technologies'